2019
DOI: 10.28945/4366
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teacher Perceptions and Motivations to ICT Use in Learning Activities in Indonesia

Abstract: Aim/Purpose: This study aims to investigate the perceptions and motivations of state senior high school teachers in rural districts in Indonesia towards ICT use in learning activities. Background: In 2013, Indonesian government launched an ICT-based curriculum known as 2013 Curriculum. According to this curriculum, ICT must be integrated into all subjects as learning resources and media. Even though there are growing numbers of research investigating teacher perceptions and motivation to ICT use in teaching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 31 publications
7
86
0
5
Order By: Relevance
“…From the finding above, the majority of English language teachers in Bengkulu have positive responses towards the possible advantages of the integration of ICT in language teaching practice, especially concerning students' engagement and learning regarding the perceived usefulness and also perceived ease of use. These results are in line with the studies which reported that teachers view the use of ICT in teaching and learning as the assistance needed by teachers to ascertain the effectiveness of teaching and learning (Almekhlafi & Almeqdadi, 2010;Mahdum, et al, 2019).…”
Section: Obstacles In Integrating Ictsupporting
confidence: 90%
See 1 more Smart Citation
“…From the finding above, the majority of English language teachers in Bengkulu have positive responses towards the possible advantages of the integration of ICT in language teaching practice, especially concerning students' engagement and learning regarding the perceived usefulness and also perceived ease of use. These results are in line with the studies which reported that teachers view the use of ICT in teaching and learning as the assistance needed by teachers to ascertain the effectiveness of teaching and learning (Almekhlafi & Almeqdadi, 2010;Mahdum, et al, 2019).…”
Section: Obstacles In Integrating Ictsupporting
confidence: 90%
“…According to the 2013 curriculum, the use of ICT has become a necessity. This policy is stated on the Regulation Number 65/2013 of the Republic of Indonesia on the Standard Process of Primary and Secondary education (Nuh, 2013, as cited in Mahdum, Hadriana & Safriyanti, 2019). To meet the goals of this new curriculum, many schools tried hard to equip ICT facilities in their schools, such as the provision of computer laboratories, projectors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ibrahim (2004), the lack of equipment and connectivity in schools especially in rural areas has been one of the biggest challenges faced by Malaysian schools. However, according to Mahdum, Hadriana and Safriyanti (2019), it is essential to examine all these barriers as it is important in improving the readiness of teachers especially in rural areas regarding ICT use in the teaching and learning activities. Thus, this study expands upon previous studies, and investigated the use of ICT in the English Language classrooms in Malaysian schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As regards to this, Qasem and Viswanathappa (2016) and Mahdum et al (2019) state that the use and appropriation of ICT in classrooms represent complex processes. They do not only depend on the quality of the infrastructure and provision or the access to resources, but also on the interest and appropriation of professors to use them pedagogically to improve their classroom work, and thus to obtain students' significant learning (Anaya et al 2012;Morffe, 2010;Salinas, 2004).…”
Section: Review Of the Literature Ict Use In Higher Educationmentioning
confidence: 99%